Introducing Sleep Hygiene to the Church of Sidang Jemaat Allah Bethlehem Congregation, Bogor, West Java - Alya Dwiana; Triyana Sari; David Limanan (Institute for Research and Community Services, 2021)
Insomnia is one of the most common health problems. Approximately one-third of adults show symptoms related to insomnia. Around 9%-15% of people have sleeping disorders dan suffer the consequences of it in the daytime, and roughly 6% suffer from diagnosed insomnia. Although the prevalence and significant effects of insomnia have been known, sleep disorders are still rarely diagnosed and receive proper treatments. Lack of sleep will create sleep debt that the body will have to compensate for by adding more sleep time in the next day. Should this compensation fail to be fulfilled, the individual will suffer from excessive sleepiness, memory problems, difficulty concentrating, and disturbances in performing daily activities. Chronic lack of sleep can also decrease memory and cognitive abilities, trigger mood disorders and even cause hallucination. The Sidang Jemaat Allah Bethlehem church (GSJA) is one of the biggest churches in Bogor. The people of GSJA’s knowledge of healthy sleep patterns and their sleep quality was unknown. Therefore, it was necessary to provide sleep health education to raise the awareness of the importance of healthy sleep patterns, both the quantity and the quality, in practicing a healthy lifestyle. We also assessed their sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The data show that out of 41 participants, 30 of them (73.11%) have poor sleep quality (score ≥ 5) and most of them were in the 71-80-year-old age group. The participants' level of understanding about sleep hygiene has increased after the event.